The role of microRNA-binding site polymorphisms in DNA repair genes as risk factors for bladder cancer and breast cancer and their impact on radiotherapy outcomes. - Teo, M; Landi, D; Taylor, C; Elliott, F; Vaslin, L; Cox, D; Hall, J; Landi, S; Bishop, D; Kiltie, A (2012)
MicroRNAs (miRNAs) are involved in post-transcriptional regulation of gene expression through binding to messenger RNAs (mRNA) thereby promoting mRNA degradation or altered translation. A single-nucleotide polymorphism (SNP) located within a miRNA-binding site could thus alter mRNA translation and influence cancer risk and treatment response. The common SNPs located within the 3'-untranslated regions of 20 DNA repair genes were analysed for putative miRNA-binding sites using bioinformatics algorithms, calculating the difference in Gibbs free binding energy (ΔΔG) for each wild-type versus variant allele. Seven SNPs were selected to be genotyped in germ line DNAs both from a bladder cancer case-control series (752 cases and 704 controls) and 202 muscle-invasive bladder cancer radiotherapy cases. The PARP-1 SNP rs8679 was also genotyped in a breast cancer case-control series (257 cases and 512 controls). Without adjustment for multiple testing, multivariate analysis demonstrated an association with increased bladder cancer risk with PARP1 rs8679 (P(trend) = 0.05) while variant homozygotes of PARP1 rs8679 were also noted to have an increased breast cancer risk (P = 0.03). In the radiotherapy cases, carriers of the RAD51 rs7180135 minor allele had improved cancer-specific survival (hazard ratio 0.52, 95% confidence interval 0.31-0.87, P = 0.01). This is the first report of associations between DNA repair gene miRNA-binding site SNPs with bladder and breast cancer risk and radiotherapy outcomes. If validated, these findings may give further insight into the biology of bladder carcinogenesis, allow testing of the RAD51 SNP as a potential predictive biomarker and also reveal potential targets for new cancer treatments.